Entre profane et sacré : Usages d’Internet et islam dans deux communautés musulmanes ouest-africaines à Montréal - Traoré, Diahara (Anthropologica, 2022)
This article, based on an ethnographic study of twenty months among West African Muslims in Montreal, explores the uses of the Internet in two West African Muslim communities. Using a framework adapted from the sacred-profane dichotomy of Emile Durkheim, this study attempts to reconstruct the modes of preservation and dismantling of the sacred and the ways in which the Internet is involved in these processes. While in the Mouride community, the Internet is used to maintian religious hierarchies and sacred spaces, another Guinean and Senegalese Islamic Center uses the Internet as a tool for democratization and secularization of religious knowledge. The study of Internet usage in these two West African communities in Montreal offers a mixed view on how to be a Muslim in the context of migration and transnationalism, and the role of new information technolo gies in the implementation of religious practices.